A matematização crítica em projetos de modelagem - Wanderley Sebastião de Freitas (2013)
This research aimed to understand how the mathematization process had developed through a modelling project that was oriented towards Critical Mathematics Education. A group of voluntary students of the third year of the technical course, that was integrated into Mechanical high school in Minas Gerais Federal Institute of Education, Science and Technology, took part in the environment built for developing this project. A qualitative methodological approach was adopted in order to investigate and analyze the empirical material produced. The accomplishment of this study was based upon authors on Mathematics Education mainly Ubiratan DAmbrósio and Skovsmose as well as those on Education, namely Paulo Freire and Giroux, whose ideas come from a common core to strengthen Education towards the human emancipation. The outcomes showed that the mathematization process was developed where ideologies from different school activities, which the students used to achieve, met one another, focusing on mathematics teaching/learning situations and, also, on disciplines of technical areas. If, on one hand, there were marks of Ideology of Certainty in the beginning of the mathematization process, issued from the traditional school mathematics, on the other hand that ideology became weaker because of the partnership between the modelling group and the new technologies, as well as the way mathematics and its uses are conceived by some disciplines of the technical areas. However, the conception of education for critical consciousness and dialogical education defended by Paulo Freire, understood to be developing the project, contributed greatly to drive the participants to analyze carefully the complex socio-economic and political relationship associated with the exploration/exploitation of minerals and the development of the towns that constitute the region of Alto Paraopeba/BR.